Pengaruh Model Pembelajaran Flipped Classroom Terhadap Keterampilan Berpikir Kritis Matematis Siswa - Susianti, Susianti; Solihah, Fatimatus; Padli, Saiful (Universitas Qamarul Huda Badaruddin, 2025)
This study aims to determine the effect of the flipped classroom learning model on junior high school students' mathematical critical thinking skills. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of eighth-grade students divided into experimental and control groups. The research instrument was a mathematical critical thinking skills test based on interpretation, analysis, inference, and evaluation indicators. Data were collected through pre-test and post-test, then analyzed using the t-test. The results showed a significant difference in mathematical critical thinking skills between students taught using the flipped classroom model and those taught with conventional learning. The flipped classroom model positively influences students' mathematical critical thinking skills.